2017
DOI: 10.1080/15384047.2017.1345386
|View full text |Cite
|
Sign up to set email alerts
|

The novel autophagy inhibitor elaiophylin exerts antitumor activity against multiple myeloma with mutant TP53 in part through endoplasmic reticulum stress-induced apoptosis

Abstract: Elaiophylin is a natural compound and a novel and potent inhibitor of late stage autophagy with outstanding antitumor activity in human ovarian cancer cells. However, the possible biologic effects and functional linkage between elaiophylin and multiple myeloma (MM) have not been explored. This study aimed to assess the effect of elaiophylin on MM cells with mutant TP53 and the possible molecular mechanism. The results suggested that elaiophylin exerted anti-myeloma activity by inducing apoptosis and proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…B,C). To test whether ER stress results in cell apoptosis in the mutant liver, TUDCA, an inhibitor of ER stress , was used to treat mutants. While TUDCA application could restore ER stress level to the normal level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…B,C). To test whether ER stress results in cell apoptosis in the mutant liver, TUDCA, an inhibitor of ER stress , was used to treat mutants. While TUDCA application could restore ER stress level to the normal level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of autophagy by Beclin-1 knockdown or treatment with autophagy inhibitors, i.e., 3-methyladenine (3-MA) and chloroquine, induces MM cells apoptosis [88] , [89] and blocks autophagosome formation. Recently, Wang et al [90] demonstrated that elaiophylin, a potent inhibitor of late stage of autophagy, has an antiā€“MM cell activity via inhibition of the autophagic flux and persistent activation of ER stressā€“mediated apoptosis. On the other hand, basal autophagy is tightly regulated to avoid autophagic cell death.…”
Section: Autophagy As Prosurvival Machinery In MMmentioning
confidence: 99%
“…Clarithromycin suppresses autophagy by inhibiting the interaction between the hERG1 potassium channel and PI3K in colorectal cancer ( Altman and Platanias, 2012 ; Petroni et al ., 2020 ). Elaiophylin, a macrolide antibiotic with immunosuppressive properties, inhibits the autophagic flux and has anti-tumor activity in ovarian cancer ( Zhao et al ., 2015 ) and multiple myeloma with mutant TP53 ( Wang et al ., 2017 ).…”
Section: Autophagy Inhibitors In Cancer Therapymentioning
confidence: 99%